HISTOLOGY AND HISTOCHEMISTRY OF THE CERVICAL OESOPHAGUS IN THE EIGHTEEN WEEKS- OLD SIRUVIDAI CHICKEN - K.Dharani; O.R. Sathyamoorthy; T.A. Kannan; K. Nagarajan (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Siruvidai chicken is an indigenous ecotype and reared as backyard poultry in Ariyalur district of Tamil Nadu state. The oesophagus is a distensible and tube shaped organ situated on the right side of neck in the birds.The present study was conducted on six numbers of 18weeks- old Siruvidai chicken.The tissues pieces from the cervical oesophagus  were  collected  and  fixed in  10  percent  neutral  buffered  formalin  and processed for histological and histochemical staining methods. The oesophagus was composed of four tunics viz., tunica mucosa, tunica submucosa, tunica muscularis and tunica serosa. The lamina epithelium was lined by stratified squamous epithelium with less keratinisation. The lamina propria contained mucous glands. The lamina muscularis was distinct. The submucosa was thin. The tunica muscularis has two layers. The tunica adventitia covered cervical oesophagus. The presence of carbohydrates in the oesophageal glands and proteins in the muscle cells of lamina muscularis and tunica muscularis layers were demonstrated by histochemical staining methods. Micrometric observations were recorded on the thickness of different layers and diameter of mucous gland of cervical oesophagus.